Working in partnership with parents: the triangular connection - Maayan Burstein (Scottish Journal of Residential Child Care)
Modern residential care in Israel can trace its history back to the end of the Second World War. At that time, orphaned Jewish children were sent to Palestine for refuge, and as part of the building of a Jewish society in the future. There were also children who were not orphans, but were sent by their families. When the families arrived in Palestine, structures called caring communities were perceived as the ideal institutions in which to raise children. The caring communities took the place of the family, in many cases.